Mapping of Pedagogical Practices in Nature Sciences Developed in the Context of PIBID in Qualis Journal Articles A and B (Research, Society and Development, 2022)
This research aimed to map the papers on pedagogical practices under the PIBID, which involved the subprojects in the area of Nature Sciences. The research was conducted in national journals in the area of science education with Qualis A1, A2 and B1, between 2009 and 2019. A total of 298 articles were found, from which only articles that brought the description of the practices carried out in the body of the text were selected. In this sense, only 56 articles met the criterion. The general analysis of these articles shows that: no articles meeting the criteria were found in the A1 journals; the journals Experiências em Ensino de Ciências (UFRGS) and Química Nova na Escola were those that most published articles that met the stipulated criteria; there is a predominance of the areas of Chemistry and Biology; there is a greater amount of pedagogical practices published in high school; public institutions are those that most produce knowledge in the area; the authors who publish on the theme are diverse; the format of intervention in the school is often not explicit; and that few actions were developed in the afterschool period.